Paracoccus denitrificans PD1222 utilizes hypotaurine via transamination followed by spontaneous desulfination to yield acetaldehyde, and finally acetate for growth - Felux, Ann-Katrin; Denger, Karin; Weiss, Michael; Cook, Alasdair M.; Schleheck, David (My University, 2013)
Hypotaurine (HT, 2-aminoethane-sulfinate) is known to be utilized by bacteria as a sole source of carbon, nitrogen and energy for growth, as is taurine (2-aminoethane-sulfonate), however, the corresponding HT-degradation pathway remained undefined. Genome-sequenced Paracoccus denitrificans PD1222 utilized HT (and taurine) quantitatively for heterotrophic growth and released the HT-sulfur as sulfite (and sulfate), and HT-nitrogen as ammonium. Enzyme assays with cell-free extracts suggested that a HT-inducible HT:pyruvate aminotransferase (Hpa) catalyzes the deamination of HT in an initial reaction step. Partial purification of the Hpa activity and peptide fingerprinting-mass spectrometry (PF-MS) identified the Hpa-candidate gene; it encoded an archetypal taurine:pyruvate aminotransferase (Tpa). The same gene-product was identified via differential PAGE and PF-MS, as well as the gene of a strongly HT-inducible aldehyde dehydrogenase (Adh). Both genes were overexpressed in E. coli. The overexpressed, purified Hpa/Tpa showed HT:pyruvate-aminotransferase activity. Alanine, acetaldehyde, and sulfite, were identified as the reaction products, but not sulfinoacetaldehyde; the reaction of Hpa/Tpa with taurine yielded sulfoacetaldehyde, which is stable. The overexpressed, purified Adh oxidized the acetaldehyde generated during the Hpa reaction to acetate in an NAD+-dependent reaction. Based on these results, the following degradation pathway for HT in strain PD1222 can be depicted. The identified aminotransferase converts HT to sulfinoacetaldehyde, which desulfinates spontaneously to acetaldehyde and sulfite; the inducible aldehyde dehydrogenase oxidizes acetaldehyde to yield acetate, which is metabolized, and sulfite, that is excreted.
Keywords: 570